2011
DOI: 10.13181/mji.v20i3.454
|View full text |Cite
|
Sign up to set email alerts
|

Zinc supplementation could modulate T cell to maintain interleukin-2 level in seropositive contact of leprosy patients

Abstract: Latar belakang: WHO mencatat jumlah penderita kusta di Indonesia menduduki peringkat ketiga di dunia setelah India dan Brazil. Jumlah penderita kusta baru cenderung meningkat kemungkinan karena yang seropositif kusta telah berubah menjadi manifest klinis. Penelitian ini bertujuan untuk mengetahui pengaruh suplementasi seng terhadap kadar interleukin 2 (IL-2) pada narakontak kusta yang seropositif dengan status seng marjinal. Metode: Dua puluh dua orang berusia 20-40 tahun ikut dalam penelitian ini. Kelompok ya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
4
0
3
Order By: Relevance
“…It must be noted that participants of included studies in our meta-analysis on the effect of Zn treatment on IL-2 level were from people with a low concentration of serum/plasma Zn. Moreover, other ex vivo studies revealed that Zn supplementation had increasing effect on IL-2 production in Zn-deficient subjects (47,51) . Therefore, it seems that Zn supplementation corrected the low level of IL-2 as an antiinflammatory agent.…”
Section: Discussionmentioning
confidence: 97%
“…It must be noted that participants of included studies in our meta-analysis on the effect of Zn treatment on IL-2 level were from people with a low concentration of serum/plasma Zn. Moreover, other ex vivo studies revealed that Zn supplementation had increasing effect on IL-2 production in Zn-deficient subjects (47,51) . Therefore, it seems that Zn supplementation corrected the low level of IL-2 as an antiinflammatory agent.…”
Section: Discussionmentioning
confidence: 97%
“…19 On the other hand, zinc supplementation could modulate T cell to maintain IL-2 level in seropositive contact of leprosy patients. 20 Zinc deficiency may interrupt the process of signal transduction of T cell. The role affects to the lymphocite protein tyrosine kinase/ LcK, protein kinase C and extracellular regulated kinase/ Erk.…”
Section: Discussionmentioning
confidence: 99%
“…9,12- 15 Penelitian sebelumnya meneliti pengaruh suplementasi seng terhadap kadar IL-2 pada narakontak kusta yang seropositif menggunakan dosis 40 miligram seng/hari selama 3 bulan didapatkan hasil kadar IL-2 pada kelompok yang menerima seng dibandingkan dengan kelompok plasebo berbeda bermakna pada kedua kelompok (p=0,037). 13 Penelitian public health terdahulu yang dilakukan Rahfiludin terhadap narakontak pasien kusta di Jawa Timur dan Jawa Tengah menyatakan terdapat korelasi antara kadar IgM anti PGL-1 dan kadar Seng. 14 Terdeteksinya kusta subklinis serta pemberian suplementasi pada narakontak dapat digunakan sebagai dasar, diharapkan dapat memutus rantai penularan penyakit kusta.…”
unclassified